Photographer featured at gallery exhibit (Raton, NM Raton Range, 1996)
Article is about featuring different artist every month in the Continuing Artist Show.
Newspaper article
Master list item #: 98
File location is in the Raton file Cabinet
Keywords: Lind, Richard -- Artist; Ray-Vogue School of Photography; Old Pass Gallery; Art Exhibit; Art Promotion; Art Workshops; Raton, New Mexico